Wybrane problemy dotyczące pomyślnego wdrożenia systemu z bazą wiedzy - Iwasieczko, Beata (Problems of Effective Implementation Knowledge Base System, 2005)
The principal objective of this article is to answer the question about the main factors, which determine the effective implementation knowledge base system in managerial accounting.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 379-388